Normal Families and Growth of Meromorphic Functions with Their Kth Derivatives - Jianming Qi; Fanning Meng; Wenjun Yuan (Journal of Function Spaces)
Relying on the normal family theory, we mainly study uniqueness problems of meromorphic functions and their kth derivatives and estimate sharply the growth order of their meromorphic functions. Our theorems improve some previous results.